Answer:
solution is (- 3, 5 )
Step-by-step explanation:
given the 2 equations
6x - y = - 23 → (1)
8x + 3y = - 9 → (2)
rearrange (1) expressing y in terms of x
y = 6x + 23 → (3)
Substitute y = 6x + 23 into (2)
8x + 3(6x + 23 ) = - 9
8x + 18x + 69 = - 9
26x + 69 = - 9 ( subtract 69 from both sides )
26x = - 78 ( divide both sides by 26 )
x = - 3
substitute x = - 3 into (3)
y = (6 × - 3 ) + 23 = - 18 + 23 = 5
solution is (- 3, 5 )
Answer:
48sq^2
Step-by-step explanation:
(12*8)/2
96/2
48
Answer:
I deserve brainliest just as all good boys deserves fudgeeeeee
Step-by-step explanation:
v^2 = 25/81
v= the square root of 25/81 = 5/9
since that isn't a choise, don't simplify.
D works too because negative x negative = positive
CCCCCCC
Answer:
2 hours
Step-by-step explanation:
one fourth of 8 hours is 2 hours. Divide 8 by 4
4/12 plus 9/12 =15/12=1 3/12 = 1 1/4